Kajian Komunitas Ikan Dalam Aplikasinya Bidang Ekologi Perairan - Silaen, Sri Natalia (LPPM Universitas HKBP Nommensen, 2022)
Indonesia is one of the developing countries in Asia. As a developing country, Indonesia always strives to advance development in all fields including agriculture in a broad sense. The aim of economic development is to increase and expand employment opportunities, increase income, reduce poverty and simultaneously improve people's welfare. The purpose of this research was to determine the effect of partial land area on fish production, to determine the effect of the number of seeds partially stocked on fish production, to determine the effect of land area and the number of seeds stocked together on fish production. Coastal areas have a variety of potentials, including primary food sources containing protein (especially animal protein derived from fish, shrimp and the like), oil, gas and other mineral wealth that has potential in the fields of mining, tourism, settlements and industrial development.